EVALUASI KESESUAIAN LAHAN SEBAGAI UPAYA PENINGKATAN PRODUKSI TANAMAN PANGAN DI KECAMATAN KASIHAN KABUPATEN BANTUL - Wijaya, Yoram Gehing; Budiyanto, Susilo; Purbajanti, Endang Dwi (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Evaluation of land suitability was carried out in Kasihan District to determine the land suitability class for food plants. This research was conducted to determine the limiting factors that resulted in a decrease in soil fertility in the local area. Land suitability classes were obtained in S3, and N classes with limiting factors for water availability (wa), erosion hazard (eh), root media (rc), and nutrient retention (nr). The limiting factors that are found in the study area are the erosion hazard, soil pH, and organic C levels. Improvement efforts as an agricultural area development that can be done are making bunds to reduce slopes, giving biochar to increase organic C levels, and reducing soil pH. The limiting factors of soil texture and depth cannot be repaired. Soil texture is a property of the soil that is influenced by nature and is very difficult to change, and the depth of the soil cannot be changed unless other agricultural commodities are selected.